Teacher Efforts to Overcome Students' Learning Difficulties in Islamic Religious Education - Riza Safitri; M. Yusuf Ahmad; Syahraini Tambak (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This study investigates the efforts of Islamic Religious Education (IRE) teachers to overcome students' learning difficulties at SMP Negeri 1 Pekanbaru, Riau Province, Indonesia. Despite teacher efforts, persistent symptoms of learning difficulties—including slow task completion, low academic achievement among ostensibly active students, and difficulty comprehending instructional material—motivated systematic investigation of applied pedagogical strategies. Materials and methods: A qualitative descriptive research design was employed. The study involved three IRE teachers as key informants, supplemented by the school principal, vice-principal for student affairs, and counseling teachers as supporting informants. Data were collected through structured interviews, participatory observation, and documentation. Interactive model data analysis (Miles & Huberman) encompassed data reduction, data display, and conclusion drawing/verification. Results: Of fourteen identified teacher-effort indicators, five were consistently well-implemented: (1) reviewing students' personal records, (2) evaluating student assignments to monitor development, (3) identifying learning difficulty cases, (4) organizing instructional materials systematically, and (5) administering remedial programmes. Nine remaining indicators were partially implemented, including home visits, comparative progress monitoring, individualized/group tutoring, and parental collaboration. Conclusions: IRE teachers at SMPN 1 Pekanbaru have adopted several structured efforts to address student learning difficulties; however, implementation remains incomplete. Gaps in home visitation and individualized tutoring indicate systemic resource and time constraints. Strengthening teacher professional development and institutional support systems is recommended to close implementation gaps.